A state-of-the-art review on innovative glazing technologies. (January 2015) - Cuce, Erdem; Riffat, Saffa B.
Abstract: Buildings play an important role in greenhouse gas emissions since they constitute a large proportion of the global energy demand. This dramatic scenario is usually a consequence of poor thermal insulation characteristics of building fabric. Among the elements of a typical building envelope, windows are responsible for the greatest energy loss due to their notably high overall heat transfer coefficients ( U -values). About 60% of heat loss through the fabric of residential buildings can be attributed to the glazed areas. Windows are useful multifunctional devices for buildings which provide passive solar gain, air ventilation and also the ability to view the outside. However, they greatly dominate the heating and cooling demand of buildings in winter and summer, respectively. Conventional window technologies tend to have poor U -values which cause significant heat losses during the winter season and undesired heat gain in summer. Unique glazing technologies are therefore required to improve visual and thermal comfort of the occupants, whilst mitigating the energy consumption of buildings. In the present work, a comprehensive review of the latest developments in glazing technologies is presented. Currently available high performance glazing products and technologies are analyzed in detail with application examples.